Assessment for learning practices and competency among Malaysian university lecturers: a national study - Tunku Ahmad, Tunku Badariah; Zubairi, Ainol Madziah; Ibrahim, Mohd Burhan; Othman, Joharry; Nik Abdul Rahman, Nik Suryani; Abd Rahman, Zainurin; Nordin, Mohamad Sahari; Mohd Noor, Zainab (University of Cumbria, UK, 2014)
This paper reports the findings of a national study involving 534 lecturers from 33 higher learning institutions in Malaysia to find out their self-reported practices and perceived competencies in assessment for learning. Data were collected using a 24-item assessment practice inventory drawn from five of the six standards stipulated in an established USdeveloped assessment competency framework for teachers. Principal Component Analysis (PCA) and descriptive statistics were used to analyse lecturers’ reported practices and competencies. The PCA procedures extracted four underlying dimensions of AfLpractice among the lecturers that corresponded to four of the five standards used. Further descriptive analysis produced a rank order of the four AfLdimensions in terms of practice and competency. Lecturers reported to quite frequently practise‘communicating results and feedback to students’ and ‘using diverse AfL methods’. They also perceived to be more competent in these two aspects than in AfLcompliant grading practices and recognising unethical uses of assessment information. The findings produced adequate empirical support for instructional interventions and training to be provided at the national level to upgrade lecturers’ current competencies in assessment and support their adoption of AfL.